Efficacy of talc pleurodesis for malignant and paramalignant pleural effusion: a retrospective analysis of 61 cases - Hasan Oğuz Kapıcıbaşı (SERNEV, 2020)
Introduction: Malignant-paramalignant effusions are common after malignancies. Treatment of malign-paramalignant pleural effusion is directed towards palliation of symptoms and improvement in quality of life. Chemical pleurodesis has been widely used to control malignant and para-malignant pleural effusion. The present study aims to reveal the effects of chemical pleurodesis on malignant and paramalignant pleural effusions commonly coexisting with malignant diseases.Methods: 61 patients were retrospectively examined between October 2017 and December 2019. Drainage with 8F intrapleural catheter and chemical pleurodesis (sterile talc powder) were employed in 61 patients with malignant and/or paramalignant effusion. The patient group consisted of patients treated at the thoracic surgery service or consulted from other services. The patients demographics and data on their operated side (left/right), recurrence rate, length of postoperative hospital stay, and complications were extracted from their files.Results: The sample consisted of 48 male (78.6%) and 13 female (21.3%) patients. The patients were between 22 and 82 years and the average age was 60.0 ± 13.2 years. 33 patients (54.0%) were operated on the right side, while 7 (11.4%) and 21 (34.4%) were operated bilaterally or on the left side, respectively. The most common cause of malignant and paramalignant pleural effusion was found to be lung cancer, accounting for 38 (62.2%) of the patients. Postoperative recurrence was observed in 15 (24.5%) patients. The ‎Mann-Whitney U test was used for skewed variables, and the Chi-Square test (or Fisher's exact test) was used for ‎categorical variables. No significant difference was observed in terms of surgery side (p=0.676), gender (p=0.156) and malignant disease (p=0.979).The average length of hospital stay was 5.3 days.Conclusions: The primary principle is to control the symptoms by removing the intrapleural effusion in the cases of malignant and paramalignant effusions. When recurrence rates were evaluated, intrapleural catheter drainage and chemical pleurodesis are an effective and safe method in selected patients.